2010
DOI: 10.1021/cb900266r
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Biology and Chemistry of Sialic Acids

Abstract: Sialic acids are a subset of nonulosonic acids, which are nine-carbon alpha-keto aldonic acids. Natural existing sialic acid-containing structures are presented in different sialic acid forms, various sialyl linkages, and on diverse underlying glycans. They play important roles in biological, pathological, and immunological processes. Sialobiology has been a challenging and yet attractive research area. Recent advances in chemical and chemoenzymatic synthesis as well as large-scale E. coli cell-based productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
429
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 498 publications
(436 citation statements)
references
References 154 publications
2
429
1
4
Order By: Relevance
“…Glycan 20, which is an ␣2-6 monosialylated derivative of NA2, bound RCA-I before and after neuraminidase, although binding was not enhanced after neuraminidase treatment. RCA-I bound weakly to ␣2-6-sialylated lactose and LNnT (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), unlike the corresponding ␣2-3-sialylated lactose and LNnT (41-57), which were not bound. Although most sialic acid derivatives moderately decreased RCA-I binding to NA2, ␣2-6-sialylation with Neu5Ac8Me (19) and Neu5Gc9Ac (25) greatly inhibit RCA-I binding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycan 20, which is an ␣2-6 monosialylated derivative of NA2, bound RCA-I before and after neuraminidase, although binding was not enhanced after neuraminidase treatment. RCA-I bound weakly to ␣2-6-sialylated lactose and LNnT (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), unlike the corresponding ␣2-3-sialylated lactose and LNnT (41-57), which were not bound. Although most sialic acid derivatives moderately decreased RCA-I binding to NA2, ␣2-6-sialylation with Neu5Ac8Me (19) and Neu5Gc9Ac (25) greatly inhibit RCA-I binding.…”
Section: Resultsmentioning
confidence: 99%
“…in chemoenzymatic synthesis of sialosides containing natural and non-natural sialic acid residues using multiple promiscuous sialoside biosynthetic enzymes (5,(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sialic acid modification on cell surface glycoproteins and glycolipids plays a crucial role in many biological processes, including cell adhesion, antigen recognition and signal transduction [17]. Studies have shown that sialylated glycans have a good prospect in food, especially the developing nervous system in infants [18].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of Sia is catalyzed by a family of 20 sialyltransferase enzymes, which transfer Sia via 2-3, 2-6 and 2-8 linkages to various glycan acceptors [46]. The disruption of sialyltransferase genes in mice often results in immune and hematologic phenotypes [47][48][49].…”
Section: 2-3 Sia-transferase IIImentioning
confidence: 99%